The Relationship Between Competence and Skills with Nurses’ Performance in Providing Nursing Care: A Correlational Study - Daviq Ayatulloh (Indonesian Academia Health Sciences Journal, 2025)
Introduction: Nurses’ performance in providing nursing care is influenced by multiple professional factors, including competence and clinical skills. Understanding the relationship among these variables is essential to improve healthcare quality and patient safety in hospital settings. This study aimed to examine the relationship between competence and skills with nurses’ performance in providing nursing care. Methods: A quantitative correlational study with a cross-sectional design was conducted among 172 nurses working in various hospital units. Data were collected using validated structured questionnaires measuring competence, clinical skills, and performance. Descriptive statistics were used to summarize respondent characteristics and variable distributions. Cross-tabulation and Chi-square tests were applied to determine the association between variables, with a significance level set at p < 0.05. Results: Most nurses demonstrated moderate competency (39.0%) and moderate skills (39.5%), while performance was predominantly categorized as adequate (40.7%). Chi-square analysis revealed a statistically significant association between competency and performance (χ² = 148.32, df = 4, p < 0.001). Similarly, a significant relationship was found between skills and performance (χ² = 136.47, df = 4, p < 0.001). Nurses with higher levels of competence and skills were more likely to demonstrate good performance. Conclusion: Competence and clinical skills are significantly associated with nurses’ performance in providing nursing care. Strengthening competency-based development and continuous skills training may enhance performance outcomes and support improved healthcare quality.